Ambient biomass smoke and cardio-respiratory hospital admissions in Darwin, Australia - Bailie Ross S; Johnston Fay H; Pilotto Louis S; Hanigan Ivan C (BMC, 2007)
Abstract Background Increasing severe vegetation fires worldwide has been attributed to both global environmental change and land management practices. However there is little evidence concerning the population health effects of outdoor air pollution derived from biomass fires. Frequent seasonal bushfires near Darwin, Australia provide an opportunity to examine this issue. We examined the relationship between atmospheric particle loadings <10 microns in diameter (PM10), and emergency hospital admissions for cardio-respiratory conditions over the three fire seasons of 2000, 2004 and 2005. In addition we examined the differential impacts on Indigenous Australians, a high risk population subgroup. Methods We conducted a case-crossover analysis of emergency hospital admissions with principal ICD10 diagnosis codes J00-J99 and I00-I99. Conditional logistic regression models were used to calculate odds ratios for admission with 10 μg/m3 rises in PM10. These were adjusted for weekly influenza rates, same day mean temperature and humidity, the mean temperature and humidity of the previous three days, days with rainfall > 5 mm, public holidays and holiday periods. Results PM10 ranged from 6.4 - 70.0 μg/m3 (mean 19.1). 2466 admissions were examined of which 23% were for Indigenous people. There was a positive relationship between PM10 and admissions for all respiratory conditions (OR 1.08 95%CI 0.98-1.18) with a larger magnitude in the Indigenous subpopulation (OR1.17 95% CI 0.98-1.40). While there was no relationship between PM10 and cardiovascular admissions overall, there was a positive association with ischaemic heart disease in Indigenous people, greatest at a lag of 3 days (OR 1.71 95%CI 1.14-2.55). Conclusion PM10 derived from vegetation fires was predominantly associated with respiratory rather than cardiovascular admissions. This outcome is consistent with the few available studies of ambient biomass smoke pollution. Indigenous people appear to be at higher risk of cardio-respiratory hospital admissions associated with exposure to PM10.